Efektivitas Media Promosi Kesehatan Tentang Perilaku Hidup Bersih Dan Sehat (PHBS) - Nuha An Nabilah Mufidah; Atik Qurrota A’yunin Al Isyrofi; Savira Awliya Abdullah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Clean and Healthy Living Behavior (PHBS) are all health behaviors carried out out of personal awareness so that the family and all its members are able to help themselves in the health sector and have an active role in community activities. The main goal of the PHBS movement is to improve the quality of health through an awareness-raising process which is the beginning of the contribution of individuals in living a clean and healthy daily life. the average percentage of PHBS in Surabaya city households is 75.07%, this figure has reached the target of PHBS in East Java province households of 53%, however, there is still the lowest working area of ​​the health center, namely the Krembangan Selatan health center with a percentage of 48%. . This type of research is Literature Review or literature review. Literature review is what the author does by searching various sources related to a particular topic which can be obtained from various sources such as journals, archive books, articles, the internet, or other documents that are revered. the provision of knowledge through counseling and training with a combination of Leaflet media is very influential on changes in knowledge. there is a positive and significant effectiveness of animaker-based animated videos on clean and healthy living behavior. It can be seen and proven from the results of the Pearson correlation coefficient at a significance level of 5% or 0.05, namely: 0.538. One effort that can be done is to provide counseling through health promotion media that is used so that it is easy to understand and interesting to look at, and can relate to the level of target knowledge.